Optimizing Teacher Performance through Internalization of Maslow and Herzberg’s Motivation Theories - Aura Vista Prasasti; Mulyawan Shafwandy Nugraha (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2026)
This study aims to analyse the application of Maslow’s and Herzberg’s motivation theories in improving teacher performance at Madrasah. The research adopts a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving teachers and the headmaster. The findings indicate that teachers' work motivation is predominantly influenced by intrinsic factors, social climate, and religious values rather than financial incentives. Verbal appreciation from the headmaster, social cohesion among teachers, harmonious relationships with students, and the religious meaning of teaching as an act of worship are the key drivers of work enthusiasm. Analysis using Maslow's hierarchy of needs revealed that most teachers have reached the level of self-actualization, while Herzberg’s two-factor theory emphasized that motivators have a more substantial influence than hygiene factors. The study resulted in the development of an Integrative-Religious Work Motivation Model, which emphasizes strengthening intrinsic motivation, fulfilling social-hygiene needs, and fostering transformative-religious leadership. The study recommends that future research focus on the development of motivation measurement instruments based on Islamic values and conduct comparative studies across different Islamic educational institutions to better understand the broader applicability of these motivational frameworks. Additionally, exploring the role of school leadership in nurturing a supportive and motivating work environment could provide valuable insights for further enhancing teacher performance in Madrasah settings.